Pengaruh Ekstrak Bunga Rosella (Hibiscus sabdariffa L.) Terhadap Kadar Asam Urat Pada Tikus Putih (Rattus norvegicus) Yang Diinduksi LDL - Fariza, Ifat; Ramadhan, Achmad; Sutrisnawati, Sutrisnawati; Mawaddah, Hayyatun; Rauf, Abd; Trianto, Manap (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of Rosella flower extract (Hibiscus sabdariffa L.) on uric acid levels in White Rats (Rattus norvegicus) induced by LDL. The research method used is the Laboratory experiment method with a Completely Randomized Design (CRD) pattern. The number of samples used was 21 White Rats consisting of 7 treatment groups and 3 replications. The normal control group (KN) is a group that is only given food and drink, the negative control group (K-) is given LDL induction for 30 days, the positive control group (K+) is given LDL induction for 30 days and allopurinol, and the group given LDL induction for 30 days and Rosella flower extract, namely concentrations of 25% (PI), 50% (PII), 75% (PIII), and 100% (PIV) for 14 days. The data obtained were tabulated and analyzed using one-way ANOVA statistical test using SPSS version-30. The results showed that Rosella flower extract had a significant effect (p <0.05) on reducing uric acid levels. The effective concentration for reducing uric acid levels is a concentration of 50% (PII) compared to concentrations of 75% and 100% because there are chemical compounds that are antagonistic to the active compound, thus reducing the extract's ability to reduce blood uric acid levels. The results of the Rosella flower study can reduce uric acid levels so that it can be used as an alternative natural treatment.